(untitled) (Archives of Criminology, 2023)
The prison system in the Czech Republic has been carrying out a reform process since the end of the communist regime, and has gone through more than 30 years transformation, based on an effort to become a modern European correctional system. Part of this change is the transformation of pastoral care, which is presented as one of the key pillars of penitentiary (and also post-penitentiary) care in the Czech Republic. This text is focused on the historically changing role of prison chaplains in the process of release preparation and rehabilitation of inmates in Czech post-communist prisons. Our aim is to compare official declarations, which are reproduced in written documents, with everyday practice from the perspectives of three different groups of prison world participants. This study is based on ethnographic research conducted in Czech male prisons. The data corpus includes qualitative interviews with selected actors of the prison world (prison chaplains, inmates, and representatives of prison management), material gathered through observations inside prisons, and an analysis of the documentation on the Czech penitentiary system. We found out that prison chaplains have become an integral part of the Czech prison world, but their position is still specific in comparison with the rest of prison staff. In our study, we will focus on the historical evolution of the position of prison chaplains within the organizational structure of prisons, specifics of their work with inmates, and interactions with other prison actors.